Da pornografia: os diários de Bruna, Marise e Gabriela: as prostitutas letradas - Bittencourt, Gustavo Henrique Ferreira (2008)
This dissertation establishes some reading, in the field of social sciences, which has pornography and prostitution as subject - having as main reference the diaries of the prostitutes Bruna Sufistinha, Marise and Gabriela. We have accessed some other literary works through Marquee de Sade, Henry Miller, Georges Bataille and Michel Houellebecq, in order to understand some aspects of the pornographic language. We also analyzed other contemporary discourses on the experience of pornography in cinema and on internet. It is a reflection about sexuality and what is considered obscenity. With observations on the literature of Anaïs Nin, Pauline Réage, and Hilda Hilst we tried to understand the feminine poetic point of view so that we can think about pornography and prostitution